USE OF METFORMIN TO PROLONG GESTATION IN PRETERM PRE-ECLAMPSIA: A PROSPECTIVE COHORT STUDY (Journal of Medical & Health Sciences Review, 2025)
Background: Preterm pre-eclampsia (PPE) is a serious pregnancy complication characterized by hypertension and proteinuria before 37 weeks of gestation, leading to significant maternal and fetal morbidity and mortality. Objective: This study aimed to evaluate the effect of metformin, in combination with conventional treatment, on prolonging gestation in women diagnosed with preterm pre-eclampsia (PPE). Methods: A randomized controlled trial was conducted at Gynae Unit I, Sir Ganga Ram Hospital, Fatima Jinnah Medical University, Lahore, Pakistan from 17 March 2025 to 20 June 2025 . A total of 60 women with preterm pre-eclampsia, aged between 26+0 and 31+6 weeks, were randomly assigned to two groups: one received metformin (3g/day) in addition to conventional treatment, and the other received conventional treatment only. Results: The metformin group experienced a significant prolongation of gestation (16.2 ± 4.1 days) compared to the conventional treatment-only group (4.9 ± 3.5 days), with a p-value of